Pengaruh Suhu dan Lama Fermentasi terhadap Kualitas Water Kefir Sari Labu Air (Lagenaria Siceraria) - Igirisa, Nurain; Bait, Yoyanda; Antuli, Zainudin (Program Studi Teknologi Pangan, 2022)
This research aimed to determine the effect of temperature and duration of fermentation on the quality of Water kefir calabash juice. This research used a Completely Randomized Design (CRD) with 2 factors, namely temperature (T) (±30oC and ±4oC) and fermentation time (A) (18 hours, 20 hours, 22 hours) which was repeated 3 times for each treatment. Data were analyzed using Mikrosoft Exel 2010 program. The results of data analysis were tested by statistical analysis of variance (ANOVA) with a level of a = 0.05. The results showed that the temperature and duration of fermentation did not have an effect (P0.05) on the quality of Water kefir water with calabash juice in this research. The characteristics of Water kefir with calabash juice included: pH 4, 0.72% alcohol, 1.7x106 CFU/ml total lactic acid bacteria (LAB), organoleptic testing, which included color 5,2, aroma 5,9, and taste 5,3, the results showed that the best treatment of organoleptic result indicated by treatment with a temperature of ±30oC and a fermentation time of 22 hours.